Physiological and hygienic factors in maintaining the health of schoolchildren in the educational environment - Мuxtoralieva , Jasmina; Maxmudjonova , Zuxra (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article examines the physiological and hygienic factors influencing the preservation of schoolchildren’s health in the educational environment. Special attention is given to the analysis of learning conditions, daily routine, level of physical activity, and sanitary-hygienic requirements for the organization of the educational process. The impact of adverse factors such as fatigue, physical inactivity, poor posture, and visual impairment on students’ overall health is discussed. The necessity of a comprehensive approach to creating a health-preserving educational environment is substantiated, including the rational organization of learning activities, compliance with hygiene standards, and the development of healthy lifestyle habits among students. The article concludes that effective cooperation between teachers, parents, and healthcare professionals plays a key role in maintaining and strengthening children's health.